2022
DOI: 10.3389/fvets.2022.1087693
|View full text |Cite
|
Sign up to set email alerts
|

Center of pressure and ground reaction forces in Labrador and Golden Retrievers with and without hip dysplasia at 4, 8, and 12 months of age

Abstract: Canine hip dysplasia (CHD) is a common orthopedic disease. Owing to the importance of CHD in affected dogs, both clinically and for their use in breeding or work, increasing attention is being given to early diagnosis. Therefore, early clinical and radiological examination of young animals is increasingly in demand, whereas common CHD screening according to the Fédération Cynologique Internationale (FCI) is usually performed at the age of 12 months or even older in Europe. One way to objectively evaluate gait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore, the ability to restore balance is directly influenced by the position of the COP prior to perturbation (35). The COP can be measured easily using force and pressure measurement plates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the ability to restore balance is directly influenced by the position of the COP prior to perturbation (35). The COP can be measured easily using force and pressure measurement plates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Previous evaluations in veterinary medicine were performed during static posturography, that is, during quiet standing with (11-16, 22, 24, 31) and without challenging PS (23), and during gait analysis in normal locomotion (10,20,21) and different tasks (17,18). Moreover, the COP of the body (11, 14-16, 22, 23, 31) and that within the paws (10,12,13,(17)(18)(19)(20)) can be measured. Some measurements are conducted with the animal standing on a plate with all feet to calculate the body COP (11,16,22,23,31), whereas others evaluate it only between the forelimbs (11,14,15,31) or hindlimbs (11,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrillo et al [ 17 ] demonstrated a higher sway in lame dogs with CCL rupture and elbow dysplasia compared to healthy ones; hence, muscle strength could be of importance for balance control in dogs with stifle injury. Recent studies [ 18 , 19 , 20 , 21 ] measured postural sway by observing changes in the center of pressure (COP), using force or pressure plates, in both the mediolateral and craniocaudal directions. Lutonsky et al [ 19 ] used three-dimensional circular movements to challenge standing balance in healthy dogs and found a significant increase in multiple COP parameters with greater movement in the mediolateral direction than craniocaudal.…”
Section: Introductionmentioning
confidence: 99%
“…Lutonsky et al [ 19 ] used three-dimensional circular movements to challenge standing balance in healthy dogs and found a significant increase in multiple COP parameters with greater movement in the mediolateral direction than craniocaudal. Dogs with arthrosis of the stifle joint have shown an increase in mediolateral movements compared to healthy dogs [ 21 ], while dogs with osteoarthritis of the elbow or hip joint indicated compensatory changes in the COP within the paws [ 20 ].…”
Section: Introductionmentioning
confidence: 99%